The Red Sea marine sponge Spongia irregularis: metabolomic profiling and cytotoxic potential supported by in silico studies. Issue 24 (17th December 2022) - Abdelaleem, Enas Reda; Samy, Mamdouh Nabil; Ahmed, Safwat A.; Aboulmagd, Asmaa M.; Alhadrami, Albaraa Hani; Rateb, Mostafa E.; Abdelmohsen, Usama Ramadan; Desoukey, Samar Yehia
Abstract: The current study discusses the chemical composition of the marine sponge Spongia irregularis using LC-HRESIMS. The metabolomic profiling resulted in the annotation of 17 metabolites of different chemical classes. Additionally, evaluation of the cytotoxic activities of the total extract and different fractions were carried out against three different cell lines where the n -butanol fraction exhibited the highest cytotoxic effects against HepG-2, MCF-7 and CACO-2 cell lines with IC50 values of 9.6 ± 0.02, 4.3 ± 0.10 and 5.6 ± 0.03 µg/mL, respectively. Also, the study was supported by docking study of the identified compounds for binding affinity to MSK1. Graphical Abstract: UF0001